Response of rocky shore communities to anthropogenic pressures in Albania (Mediterranean Sea): Ecological status assessment through the CARLIT method. Issue 1 (15th August 2016) - Blanfuné, Aurélie; Boudouresque, Charles François; Verlaque, Marc; Beqiraj, Sajmir; Kashta, Lefter; Nasto, Ina; Ruci, Stela; Thibaut, Thierry
Abstract: The lower mid-littoral and shallow subtidal communities were studied in the district of Vlora (Albania), three years after the establishment of a Marine Protected Area, with particular attention to the long-lived species. The bioconstructions built in the mid-littoral zone by the calcified rhodobiont Lithophyllum byssoides were in poor condition and sometimes even dead. In contrast, the brown alga Cystoseira amentacea constituted lush stands. For assessing the ecological status of the studied area, the CARLIT method, based upon macroalgal communities, was applied. The observed range of ecological status was wide ('high' through 'bad') and was overall among the lowest assessed to date in the Mediterranean Sea. The occurrence of extensive sea-urchin barren-grounds, though not taken into consideration by the CARLIT index, confirmed the poor condition of large sectors of the study area. Overall, the CARLIT index is well correlated with anthropogenic pressures, as assessed by the LUSI index. Highlights: First ecological assessment by the CARLIT method in Albania The ecological assessment is well correlated with the anthropogenic pressures. The Lithophyllum byssoides rims were in poor condition and sometimes even dead. The brown alga Cystoseira amentacea constituted lush stands.